On features of the life cycle of humpback shrimp Pandalus hypsinotus (Decapoda, Pandalidae) in the Tatar Strait - D. N. Yuriev (Известия ТИНРО)
The study is based on biological analyses of > 80,000 ind. of Pandalus hypsinotus collected in trawl surveys and trap fishery in the Tatar Strait in 2010–2022. Due to the lack of age-recording structures, the size-age structure of shrimp is usually determined by various statistical methods, each of which has some limitations and drawbacks. The modal analysis of size-sex composition dynamics is used in this study, including tracing the growth of strong year-classes. The analysis takes into account the dynamics of major seasonal events such as group molting, spawning, and larval hatching. The reproductive cycle of females is assumed to be 2 years. Based on results of the analysis, the life cycle of humpback shrimp in the Tatar Strait is as follows. After the larvae hatch from eggs in April-May, immature shrimp spend the first year of their life at the depths < 70 m, where they reach the carapace length of 9–15 mm, with a modal size of 11–12 mm. In the second year, they grow to the length of 20–22 mm, on average, then become males and migrate to deeper layer where join the adults. Further growth is described on the data for the strong year-class of 2010: the modal size of males reaches 26–27 mm at age 3 years, 29–30 mm — at age 4, 32–33 mm — at age 5, and 35–36 mm — at age 6. Gender transition of shrimp begins at age 5+, but most males become hermaphroditic at the age 6+. The modal size of intersex hermaphrodites ranges from 37 to 39 mm. At the age of 6 years and 9 months, the intersexes spawn en masse and transform into females. The first larval hatching of new females occurs after 15 months, i.e. at exactly 8 years of age. At least three cycles of spawning (larvae release) are assumed for females, taking into account their polymodal size composition and dynamics of their size increments per molt by age. In assumption of 2-year reproductive cycle, the female stage lasts 6 years. Thus, the total life span for the most of humpback shrimps is estimated to be 12 years (6 years before gender transition and 6 years after). Apparently, a small number of them live 14 years and spawn four times, and some can live up to 16 years and spawn five times.